2016
DOI: 10.1038/cr.2016.26
|View full text |Cite
|
Sign up to set email alerts
|

MLKL forms cation channels

Abstract: The mixed lineage kinase domain-like (MLKL) protein is a key factor in tumor necrosis factor-induced necroptosis. Recent studies on necroptosis execution revealed a commitment role of MLKL in membrane disruption. However, our knowledge of how MLKL functions on membrane remains very limited. Here we demonstrate that MLKL forms cation channels that are permeable preferentially to Mg2+ rather than Ca2+ in the presence of Na+ and K+. Moreover, the N-terminal domain containing six helices (H1-H6) is sufficient to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
107
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(123 citation statements)
references
References 50 publications
2
107
0
Order By: Relevance
“…We showed previously (26) that translocation of the artificial MLKL N-terminal domain oligomers to the plasma membrane led to ion influx and is sufficient to induce necroptosis; Hildebrand et al (35) and Dondelinger et al (27) showed that overexpression of the MLKL N-terminal four-␣-helix boundary is enough to trigger necroptosis; Wang et al (28) and Dondelinger et al (27) showed that the MLKL N-terminal four-␣-helix boundary could bind to negatively charged phospholipids and cardiolipin and disrupted the membrane integrity in the liposome. A recent work by Xia et al demonstrated the cation channel activity of MLKL in the liposome, supporting the idea that ion influx plays a role in necroptotic cell death (31). Our data demonstrate that MLKL forms a 180°rotational symmetry complex.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…We showed previously (26) that translocation of the artificial MLKL N-terminal domain oligomers to the plasma membrane led to ion influx and is sufficient to induce necroptosis; Hildebrand et al (35) and Dondelinger et al (27) showed that overexpression of the MLKL N-terminal four-␣-helix boundary is enough to trigger necroptosis; Wang et al (28) and Dondelinger et al (27) showed that the MLKL N-terminal four-␣-helix boundary could bind to negatively charged phospholipids and cardiolipin and disrupted the membrane integrity in the liposome. A recent work by Xia et al demonstrated the cation channel activity of MLKL in the liposome, supporting the idea that ion influx plays a role in necroptotic cell death (31). Our data demonstrate that MLKL forms a 180°rotational symmetry complex.…”
Section: Discussionsupporting
confidence: 73%
“…We propose that ␣-helices 1, 2, 3, and 5 but not ␣-helix 6 of MLKL are the transmembrane fragments because this is the only possibility, given the fact that the N-and C-terminal ends are at the inner side of the plasma membrane. The fact that ␣-helix 6 was detected as a transmembrane fragment in the study of Xia et al is likely because they used the N-terminal 178 amino acids of MLKL in the SCAM experiment (31). To have the C-terminal kinase-like domain of MLKL in its position of the octamer, ␣-helix 6 has to be unleashed to allow opening of the ␣-helix bundle, as suggested by published structural studies of MLKL (32,36), and thus, ␣-helix 6 is not involved in penetration of the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations